2020
DOI: 10.1037/vio0000277
|View full text |Cite
|
Sign up to set email alerts
|

Bullying and psychopathic traits: A longitudinal study with adolescents in India.

Abstract: Objectives: The goal of this three-wave longitudinal study was to examine if youth psychopathic traits, namely narcissism, callous-unemotionality (CU), and impulsivity predicted the likelihood of a student being a bully, victim, or bully victim among adolescents in India. Method: The sample consisted of 1,238 students from nine schools in Indore, India. We used self- as well as peer-reports to measure bullying and victimization behavior in the classroom, at 3 time-points in 1 school year. Psychopathic traits w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 43 publications
2
20
0
Order By: Relevance
“…It is where the students interact the most, away from any kind of supervision, thereby creating a conducive environment for bullying. The thought of seeking happiness through seeing others hurt was the perceived reason behind most of the bullying incidents in the views of the victims; these findings are in line with another study in India that reveals a non-pathologic narcissistic attitude predicts a bully (Thakkar et al, 2020a).…”
Section: Discussionsupporting
confidence: 87%
“…It is where the students interact the most, away from any kind of supervision, thereby creating a conducive environment for bullying. The thought of seeking happiness through seeing others hurt was the perceived reason behind most of the bullying incidents in the views of the victims; these findings are in line with another study in India that reveals a non-pathologic narcissistic attitude predicts a bully (Thakkar et al, 2020a).…”
Section: Discussionsupporting
confidence: 87%
“…Of the 37 studies that were included, two were longitudinal studies (Nguyen et al 2017;Thakkar et al 2020), two were experimental studies with pre-and post-test intervention designs Shinde et al 2018Shinde et al , 2020, whereas the others were cross-sectional studies. Seven of the 37 studies used peer-reports, 21 studies used self-reports, two studies used both self-and peer-reports (Chakrabartty and Gupta 2016;Thakkar et al 2020), whereas six studies used structured or semi-structured interviews and open-ended questions to collect data on bullying and victimization (Kshirsagar et al 2007;Malhi et al 2014Malhi et al , 2015Malik and Mehta 2016;Munni and Malhi 2006;Ramya and Kulkarni 2011). One study used a photo-story method (Skrzypiec et al 2015), where participants were invited to use a photograph or picture to illustrate their opinions or experiences of bullying.…”
Section: Design and Data Collectionmentioning
confidence: 99%
“…Seven studies specified that the instrument used to assess bullying behavior was an English language questionnaire, while 10 studies used either existing translations or translations created by the authors of the study, of English scales into Indian regional languages. Two studies used English instruments and orally explained the translation in Punjabi (Lee et al 2018) or translated the difficult words to Hindi (Malik and Mehta 2016), and one study used English and Hindi language translations of the scales (Thakkar et al 2020).…”
Section: Psychometric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported here is part of a larger project on bullying and victimization in Indian schools. This dataset has previously been used in a publication about psychopathy and bullying (Thakkar et al, 2019). Here, we present only the variables relevant to the current paper.…”
Section: Methodsmentioning
confidence: 99%